Characterization of clones of boolean operations by identities - Butkote, R.; Denecke, K. (Algebra and Discrete Mathematics, 2007)
In [4] the authors characterized all clones of Boolean operations (Boolean clones) by functional terms. In this paper
we consider a Galois connection between operations and equations
and characterize all Boolean clones by using of identities. For each
Boolean clone we obtain a set of equations with the property that
an operation f belongs to this clone if and only if it satisfies these
equations.